2010
DOI: 10.1007/s00296-010-1637-5
|View full text |Cite
|
Sign up to set email alerts
|

A three-way interplay of DR4, autoantibodies and synovitis in biopsy-proven idiopathic inflammatory myositis

Abstract: The aim of this study was to determine the HLA and autoantibody associations of patients with histologically confirmed idiopathic inflammatory myositis (IIM). Serum and DNA were archived from South Australian patients with biopsy-proven dermatomyositis (DM), polymyositis (PM) and inclusion body myositis (IBM). HLA typing for Class I and II alleles was performed by serology and DNA-based technology, respectively, for 133 myositis patients and 166 Caucasian population-based controls. Myositis-specific and myosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…While previous studies have reported an association between IBM and the presence of various autoantibodies, thus suggesting an autoimmune process in IBM, none have been identified as disease specific [13] and their prevalence is less than that seen with DM and PM [3] [14] [15] [16] [17]. In a review of 99 patients with sporadic IBM, 43 (44%) had elevated titers of one or more of nine different non disease-specific autoantibodies [13].…”
Section: Discussionmentioning
confidence: 92%
“…While previous studies have reported an association between IBM and the presence of various autoantibodies, thus suggesting an autoimmune process in IBM, none have been identified as disease specific [13] and their prevalence is less than that seen with DM and PM [3] [14] [15] [16] [17]. In a review of 99 patients with sporadic IBM, 43 (44%) had elevated titers of one or more of nine different non disease-specific autoantibodies [13].…”
Section: Discussionmentioning
confidence: 92%
“…The HLA-DRB1*0301 allele is strongly associated with the risk of developing autoimmune inflammatory myopathies in Caucasians (Arnett et al, 1996;Rider et al, 1998;O'Hanlon et al, 2005) and with autoantibodies, particularly the antisynthetases (Hausmanowa-Petrusewicz et al, 1997;Chinoy et al, 2006;Selva-O'Callaghan et al, 2006;Limaye et al, 2012) but previous studies have included few patients with s-IBM. We have previously reported a strong association with HLA-DRB1*03 in an Australian s-IBM cohort, as well as a correlation with age at onset and disease severity (Needham et al, 2008;Mastaglia, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Our findings confirm that there is a higher than expected incidence of nonspecific AAb such as ANA and antibodies to the nuclear antigens Ro-52, Ro-60, La and RNP, but not of organ-specific AAbs such as anti-TPO or anti-tTg or of the MSAs. Previous studies in American, Dutch and South Australian s-IBM cohorts have reported frequencies of MAAs of up to 43% of cases but the significance of these findings is uncertain as none of these studies included a population control group (Love et al, 1991;Koffman et al, 1998;Brouwer et al, 2001;O'Hanlon et al, 2006;Limaye et al, 2012). In other AAb studies, selected healthy individuals or patients with other neurological disorders were used as controls and patient and control sera were assayed in different laboratories.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have previously reported the diagnostic criteria employed to diagnose IIM. 6 The histological features recorded were the presence of polyphasic polyfocal muscle fibre necrosis with lymphocytic and macrophage myoinvasion, lymphocytic invasion of non-necrotic fibres, perivascular and interstitial lymphocytic infiltrates, up-regulation of major histocompatability complex (MHC)1 and 2, immune-staining for CD45 (lymphocytes) and CD68 (macrophages), vacuoles (rimmed and non-rimmed), perifascicular atrophy and basophilic fibre regeneration. Serum has been stored from a large number of patients.…”
mentioning
confidence: 99%